2022
DOI: 10.1371/journal.pone.0275167
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 epidemic on students’ mental health: A cross-sectional study

Abstract: Background The COVID-19 pandemic is currently one of the biggest public health threats for people’s mental health. A particularly endangered group were students, who became highly affected by measures of social distance due to their active lifestyle. Therefore, the aim of this paper is to assess the level of self-reported stress, anxiety and depression of the student population in Serbia, in relation to demographic characteristics, living and studying conditions, students’ activities during the epidemic, poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 31 publications
1
15
1
2
Order By: Relevance
“…Their findings indicate that depression, anxiety, and stress were present in 13.6%, 25.6%, and 26% of students, respectively. These values are significantly lower than those reported by the studies conducted during the pandemic (16,17) but also lower than the values obtained through our study. This clearly indicates that the pandemic has had a significant impact on the mental health of the student population.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…Their findings indicate that depression, anxiety, and stress were present in 13.6%, 25.6%, and 26% of students, respectively. These values are significantly lower than those reported by the studies conducted during the pandemic (16,17) but also lower than the values obtained through our study. This clearly indicates that the pandemic has had a significant impact on the mental health of the student population.…”
Section: Discussioncontrasting
confidence: 94%
“…Severe and extremely severe forms of depression were more common in rural areas (11.8% and 7.6%, respectively) than in urban areas (4.9% and 5.2%, respectively), while moderate depression was ten times more common in urban settlements (11.7%) than in rural settlements (1.1%). And other studies have shown similar results to ours (16,17). Contrary to our results, some studies have shown that older students have a higher frequency of depressive symptoms (28).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Studies consistently found that female students were more at risk for increased anxiety during the pandemic. The research does not firmly establish why the female gender appears at significant risk for developing anxiety and increased stress [ 8 , 9 , 14 - 16 , 18 , 20 , 28 - 32 ]. This female factor could be due to the multifaceted nature of biological, psychosocial, cultural, and behavioral differences before and during the pandemic [ 29 ].…”
Section: Reviewmentioning
confidence: 99%